2013
DOI: 10.1021/ac402649v
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Point Extraction of Plutonium in Environmental Matrixes Coupled to ICPMS and α Spectrometry in Highly Acidic Conditions

Abstract: A new cloud point extraction procedure has been developed for the quantification of plutonium(IV) in environmental samples. The separation procedure can be either coupled to inductively coupled plasma mass spectrometry (ICPMS) or α spectrometry for plutonium quantification. The method uses a combination of selective ligand (P,P'-di(2-ethylhexyl) methanediphosphonic acid (H2DEH[MDP])) and micelle shielding by bromine formation to enable quantitative extraction of Pu in highly acidic solutions. Cross-optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 46 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…[41][42][43][44]149,150 The development of green solvents and novel methodologies like cloud point extraction which reduce the amounts of radioactive waste is urgently warranted. 151 Intensive research is going on at various laboratories to satisfy these urgent requirements. Inductively coupled plasma sources used in solution based ICPMS can be investigated to prepare thin, homogeneous and quantitative sources.…”
Section: Challenges In Alpha Spectrometrymentioning
confidence: 99%
“…[41][42][43][44]149,150 The development of green solvents and novel methodologies like cloud point extraction which reduce the amounts of radioactive waste is urgently warranted. 151 Intensive research is going on at various laboratories to satisfy these urgent requirements. Inductively coupled plasma sources used in solution based ICPMS can be investigated to prepare thin, homogeneous and quantitative sources.…”
Section: Challenges In Alpha Spectrometrymentioning
confidence: 99%
“…Labrecque et al recently demonstrated the use of bromate as an agent to induce the extraction of plutonium at highly acidic pH values. 33 Bromate, in the presence of an excess of bromide, comproportionates to form bromine, which efficiently shields the micelles from the disrupting effect of high-solids matrices in highly acidic conditions. The bromine formed has a tendency to stay at the water-micelle interface, due to its high polarisability.…”
Section: †)mentioning
confidence: 99%
“…Above the CPT, the micellar solution separates into two phases: a small volume surfactant-rich phase that contains the analyte, and an aqueous phase containing a low concentration of surfactant. To date, CPE has been widely applied to the extraction of trace metal ions from various matrices through the formation and pre-concentration of chelates (Labrecque, Whitty-Leveille, & Lariviere, 2013;Silva, Roldan Pdos, & Gine, 2009;Ulusoy, Akcay, Ulusoy, & Gurkan, 2011). There are several reports of CPE as a pre-concentration step for the determination of Se by different spectrometric techniques, including spectrophotometry (Soruraddin, Heydari, Puladvand, & Zahedi, 2011;Wen, Zhang, Li, Fang, & Zhang, 2014), spectrofluorimetry (Güler, Maden, Bakırdere, Yavuz Ataman, & Volkan, 2011), graphite furnace atomic absorption spectrometry(GF-AAS) (Sun, Liu, & Wu, 2013), electrothermal atomic absorption(ET-AAS) (Ghambarian,Yamini,Saleh,Shariati,& Yazdanfar,3 2009; Li, Hu, He, & Xiang, 2008;Sounderajan, Kumar, & Udas, 2010) and electrothermal vaporization inductively coupled plasma mass spectrometry(ETV-ICPMS) (Chen, Hu, & He, 2006;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%